Budget deficits and reforms - Lahiri, Ashok K. (2000)
This paper provides an overview of the magnitude of fiscal deficit and discusses reasons for its persistence. It describes how the deficit is complicating the task of fiscal reform and suggests remedial measures. - Reproduced
Keywords: Budget deficits - India; Budget - India; Budget